2017
DOI: 10.1016/j.ibror.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of anticonvulsant efficacy and action mechanism of Mannitol vs Phenytoin in adult rat neocortical slices

Abstract: HighlightsIn cortical slices addition of 30 mM Mannitol is anticonvulsant.Mannitol decreases the rate of epileptiform discharges.As an anticonvulsant Mannitol is as effective as Phenytoin.Mannitol is already used routinely in neurointensive care.Mannitol might be used in neurointensive care also as an anticonvulsant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…An epileptic sharp-wave results from synchronization of individual EPSPs. A proposed mechanism for epileptic hypersynchrony, whether synaptic [13,14] or not (see [15], for a discussion), must provide an adequate account of the quantitative scale of synchronizing synapses and of the short time window of epileptic sharp-waves. For example, sharp-waves' amplitude is of several hundreds of microvolts, whereas the amplitude of a unitary EPSP has been estimated in the range of 0.02-0.1 μV (for examples, see simulations in [16]; and [7]).…”
Section: Low-voltage Field Potential Oscillations Preceding the Sharp-wave Prolong The Duration Of Ied Onset And May Facilitate Epilepticmentioning
confidence: 99%
“…An epileptic sharp-wave results from synchronization of individual EPSPs. A proposed mechanism for epileptic hypersynchrony, whether synaptic [13,14] or not (see [15], for a discussion), must provide an adequate account of the quantitative scale of synchronizing synapses and of the short time window of epileptic sharp-waves. For example, sharp-waves' amplitude is of several hundreds of microvolts, whereas the amplitude of a unitary EPSP has been estimated in the range of 0.02-0.1 μV (for examples, see simulations in [16]; and [7]).…”
Section: Low-voltage Field Potential Oscillations Preceding the Sharp-wave Prolong The Duration Of Ied Onset And May Facilitate Epilepticmentioning
confidence: 99%
“…Results of the assay are shown in Table 6. So far, this simple UV spectrophotometric method can be used for the estimation of Phenytoin (Bansal et al, 2017;Gujjar et al, 2017;Jouyban-Gharamaleki et al, 2017;Kopsky and Keppel Hesselink, 2017;Margiotti et al, 2017;Selioutski et al, 2017;Serafini, 2017;Sridharan and S, 2017;Teo et al, 2017;Uribe-San-Martín et al, 2017), which is validated as per ICH guidelines.…”
Section: Specificitymentioning
confidence: 99%
“…Several RG components, including aucubin, acteoside, catalpol, and mannitol, were screened to determine whether they have anticonvulsant effects, and catalpol, mannitol, and their combination were chosen for further assessment. Recently, using LiCl/pilocarpine, electroencephalography (EEG), or extracellular field recording in brain slice, some studies have reported that catalpol or mannitol might have anticonvulsant effects (Haglund and Hochman, 2005;Serafini, 2017;Gao et al, 2018), however, their roles remain unclear. In this study, their protective effects as well as that of their combination against electroshock-or chemically (PTZ or strychnine)-induced seizures, were evaluated in mice.…”
mentioning
confidence: 99%